Asymmetric Mach–Zehnder interferometer-based optical sensor with characteristics of both wavelength and temperature independence - Luo, Yanxia; Yin, Rui; Lu, Lin; Huang, Qingjie; Jiang, Shouzhen; Liu, Fengyu; Liu, Qiang; Li, Qiang (Journal of optics (New Delhi), 2023)
Optical sensors based on asymmetric Mach–Zehnder interferometer (AMZI) are very sensitive to wavelength and temperature, and their shift will affect the accuracy of measured parameters. An optical sensor based on dual AMZIs, which is independent of both optical source wavelength and ambient temperature, is presented. The designed optical sensor consists of two AMZIs cascaded, one as sensing AMZI and the other as compensating AMZI. When the wavelength and temperature change, the sensing curve of the sensing AMZI shifts, and the compensating AMZI reverses the sensing curve where it reaches a new balance without being affected by the wavelength and temperature. In this paper, the center wavelength of the optical source is 1550 nm, the shift is ± 0.1 nm, and the temperature compensation range is 5 ~ 45 °C. After compensation, the error is reduced by 2–3 orders of magnitude, and the maximum sensing error is reduced to < 0.2%. The designed sensor reduces the requirements on the optical source and ambient temperature, and greatly reduces the cost of the optical sensing system. Moreover, this compensation mechanism can be used not only for optical sensors, but also for other optical devices based on interference.